Heterogeneous adoption of quality standards in the hotel industry: drivers and effects. Issue 3 (10th April 2019) - Tarí, Juan José; Pereira-Moliner, Jorge; Molina-Azorín, José F.; López-Gamero, María D.
Abstract : Purpose: This paper aims to examine the impact of external and internal drivers on the dimensions of internalization (daily practices and continuous improvement) of quality standards, the relationship between the dimensions of internalization and their effects on customer, employee, society and organizational results in hotels. Design/methodology/approach: The study applies a structural equations analysis to test these relationships using empirical data from 176 quality-certified hotels. Findings: Hotels need internal drivers to internalize a quality system because the external drivers themselves are not able to explain significantly the quality internalization process. This paper shows the significant relationship between the dimensions of internalization (daily practices and continuous improvement) and the importance of continuous improvement (e.g. innovations from quality standards and reflection on how to improve the current work processes) for improved customer, employees, society and organizational results. Originality/value: To the best of the authors' knowledge, there are no empirical studies jointly analyzing the drivers of internalization, the relationship between the dimensions of internalization and their effects on different dimensions of results (customers, employees and society) in hotels.